Book loss in academic law libraries characteristics and comparison of related factors - Dadang, Joan B. (2007)
In spite of the safeguards and measures exercised by some selected law libraries in Manila to present possible losses of books, the problem of book loss still exists. This is clearly seen from the list of lost and/or missing books that these libraries incurred. This observation encouraged the researcher to undertake this study. Knowledge and awareness on the nature of the book losses in law libraries might help minimize, if not totally eradicate, this problem.